DINAMIKA â€˜NGAJI ONLINEâ€™ RAMADHAN DI MASA PAGEBLUK COVID-19 PADA KOMUNITAS PESANTREN - Samsul Arifin (Jurnal Kependudukan Indonesia, 2020)
This paper reveals the dynamics of the changing therapeutic relationship of the kiai with students (santri) in learning (ngaji) from face-to-face to online models in the time of COVID-19. The research method is ethnographic-hermeneutic. In the face-to-face learning system, therapeutics occur because of the warm relationship by looking directly at the kiai's face which makes the students feel calm. In the â€œNgaji Onlineâ€ the therapeutic system switches to environmental settings that make students feel safe and comfortable. In the â€œNgaji Onlineâ€ system, the warmth of relationships begins to weaken. However, this weakness can be covered up because the spiritual relationship between the kiai and the students still feels strong. This spiritual relationship is the key to therapeutic for the Islamic boarding school.